DAMPAK TINDAK PIDANA PENCUCIAN UANG TERHADAP EKONOMI MAKRO - Dian Ayu Rahmadani; Gusti Ayu Putu Wulan Rahmasari (Yayasan Nusantara Hasana Berdikari, 2023)
Money laundering is an illegal method of generating large sums of money from criminal activities, such as drug trafficking, corruption or other criminal activities. The process of money laundering generally goes through three stages of activity, namely the placement stage, the distribution stage and the collection stage with the aim of making it appear as if it comes from a legitimate source, in order to make it look clean. The emergence of losses that are reflected in the presence of victims is the adverse impact of money laundering activities which today in fact money laundering does not only have a direct impact on the individual who is harmed but the effect will be felt on national and even global economic stability. The characteristics of the crime of money laundering must be known in advance before developing a strategy to prevent and then deal with the crime of money laundering.